2018
DOI: 10.1080/09540105.2018.1444738
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory effects ofEchinaceaandPelargoniumon the innate and adoptive immunity in calves

Abstract: Immunomodulatory effects of Echinacea purpurae and Pelargonium sidoides in calves were investigated. Sixty 25-day-old nonvaccinated calves living in integrated farm unit were randomly selected and were divided into 5 treatment groups consisting of 12 calves each; 4 groups were receiving different amounts and/or times of Echinacea and Pelargonium and the control group received placebo. Blood levels of γ-interferon, cytokine gene expression, lactoferrin and total IgG were analysed on days 0, 9, and 30. When leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 65 publications
(96 reference statements)
0
7
0
Order By: Relevance
“…This can be explained by the negative feedback regulating mechanism among cytokines (Dambuza et al, 2017). In addition, we observed significantly higher serum concentrations of TGF-β1, TNF-α, IFN-γ and GM-CSF in FP than the control group, possibly because the increased concentrations of TNF-α, IFN-γ and GM-CSF promoted the production of TGF-β1, while TGF-β1 inhibited the production of TNF-α, IFN-γ and GM-CSF (Seckin, Kalayci, Turan, Yilmaz, & Yilmaz, 2018;Zhao et al, 2020). The down-regulated cytokines showing immunosuppression were observed in the PGR piglets and IUGR piglet neonates (Qi et al, 2019b ;Dong et al, 2014), but supplementation with functional bioactive substances could regulate the activity of serum cytokines and stimulate the immune function of growth retardation piglets.…”
Section: Discussionmentioning
confidence: 70%
“…This can be explained by the negative feedback regulating mechanism among cytokines (Dambuza et al, 2017). In addition, we observed significantly higher serum concentrations of TGF-β1, TNF-α, IFN-γ and GM-CSF in FP than the control group, possibly because the increased concentrations of TNF-α, IFN-γ and GM-CSF promoted the production of TGF-β1, while TGF-β1 inhibited the production of TNF-α, IFN-γ and GM-CSF (Seckin, Kalayci, Turan, Yilmaz, & Yilmaz, 2018;Zhao et al, 2020). The down-regulated cytokines showing immunosuppression were observed in the PGR piglets and IUGR piglet neonates (Qi et al, 2019b ;Dong et al, 2014), but supplementation with functional bioactive substances could regulate the activity of serum cytokines and stimulate the immune function of growth retardation piglets.…”
Section: Discussionmentioning
confidence: 70%
“…The antibacterial activity has been associated with macrophage activation determined through TNF-α and inorganic nitric oxide in macrophage cultures (Kayser et al, 2001). Additionally, P. sidoides has been used in a tablet with Echinacea purpurae increasing IgG and IFN-γ, as well as certain cytokine gene expressions, modulating immune response (Seckin et al, 2018).…”
Section: Immune-enhancing Propertiesmentioning
confidence: 99%
“…Polysaccharides, alkylamides, caffeic acid esters, and polyacetylenes are the main compounds contained in Echinacea Moench [Barnes et al 2005]. An in vivo study [Seckin et al 2018] has demonstrated improved immune response in calves receiving a medicinal preparation based on Echinacea purpurea (L.) Moench and Pelargonium sidoides DC.…”
Section: Potential Use Of Phytobiotics For Treatment and Prophylaxis mentioning
confidence: 99%